Caravanserai middens on desert roads: a new perspective on the Nabataean–Roman trade network across the Negev. (June 2022) - Bar-Oz, Guy; Galili, Roy; Fuks, Daniel; Erickson-Gini, Tali; Tepper, Yotam; Shamir, Nofar; Avni, Gideon
Abstract: Abstract : Long-distance trade routes criss-crossed ancient Africa and Eurasia. Archaeological research has focused on the commodities in transit and the excavation of major centres located along these routes, with less attention paid to smaller caravanserai and evidence such as rubbish middens. The 'Incense Route' linked the Arabian Peninsula and Red Sea to the Mediterranean Sea, with activity peaking during the Nabataean and Roman periods. The authors present the results of test-pit excavations of middens at three small Nabataean–Roman desert caravanserai along the 'Incense Route'. The assemblages recovered include material culture attesting to wide, inter-regional connections, combined with archaeobotanical and zooarchaeological data illuminating the subsistence basis of the caravan trade.